(3NdGUI GdCacGQ aj HjGf RHOI GdCSQGQs - (3GdGSaQGjjfj , eMeO Hf eMeO Hf CMeO, JGL GdOjf,J (B684 (3g` s
(3ChdgG (B:s
(3hHYO, aEf GdYdhe Ydi JTYH afhfgG, hJcKQ TLhfgG, dG jNJaj aNGeJgG, hdG jfcQ LdGdJgG s
(3BNQgG (B:s
(3hfMhgG ef GdUaGJ, afSi, hbO jJPcQ EPG de jQh Cf jbWY GddaX, hGddg CYde HGdUhGH JeJ gPg GdfSNI s
(3fSNI KGfjIs
(3GdcJGH aj TQM GdeTcd ef dH GdCdHGHs
(3GdfSNI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ LOkG aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B31 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B180s
Keywords: (3GdfMhs